Underlying factors of management practices in Czech companies - Veselý, Josef; Veselý, Štěpán (Univerzita Pardubice, 2018)
The main purpose of the present paper is to identify the factor structure of managerial approaches. Based on a survey performed in 241 Czech companies from various sectors (e.g. mechanical engineering, construction and consumer industry) we identify six factors underlying managerial practices in these companies: Strategic management, Leadership, Partners and customers, Human resources, Process management, and Knowledge and innovation. Therefore, the empirical factor structure is partially different from the theoretical five-dimensional structure assumed in the widespread EFQM model. The present paper thus improves our understanding of the interrelations among various aspects of management in Czech companies. This better understanding can in turn lead to more informed implementation of total quality management in the firms. Understanding the structure of managerial approaches typical for Czech companies can also contribute to smoother transitions when foreign managers are appointed to run Czech firms (because the structure of managerial approaches is culture-dependent, as has been shown by former research).
Keywords: managerial approaches; EFQM; quality management; survey; factor analys; C38; L20; M10